The Influence of Budget Goal Clarity and Organizational Commitment on Performance Accountability at the Regional Office XI of the Manado State Civil Service Agency - Juniawati, Veronica Lani; Wawointan, Thelma; Kantohe, Meidy (Technium Social Sciences Journal, 2025)
This study aims to examine the effect of Budget Goal Clarity (X1) and Organizational Commitment (X2) on Performance Accountability (Y), both partially and simultaneously. This research was conducted at the Regional Office XI of the Manado State Civil Service Agency (BKN). Data collection techniques using questionnaires distributed to 70 employees of the Regional Office XI BKN Manado with the census method. Respondent selection criteria are employees involved in achieving organizational performance. This research data analysis uses variant-based Partial Least Square (PLS) or components of the Structural Equation Modeling (SEM) approach and tests the effect of independent variables on the dependent variable. Data analysis using the SmartPLS application. The results showed that Budget Goal Clarity has a positive and significant effect on performance accountability. Organizational commitment has a positive and moderate effect on performance accountability. Clarity of budget objectives and organizational commitment together affect the performance accountability of the Regional Office XI of the Manado State Civil Service Agency. The coefficient of determination (R²) is 0.667, indicating that 66.7% of variability in performance accountability can be predicted through budget goal clarity and organizational commitment. Meanwhile, external factors that were not studied contributed 33.3% to the variation that occurred.